Zmiany barwnikowe siatkówki u osób z polipowatością rodzinną gruczolakowatą - Cymerys, Elżbieta; Pecold, Krystyna; Paszkowski, Jacek; Banasiewicz, Tomasz; Krokowicz, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: The aim of study was to evaluate retinal changes in patients diagnosed with familial adenomatous polyposis (FAP) and in patients with family history of FAP. Material and methods: The study was conducted on 51 patients diagnosed with FAP and 35 subjects with family history of FAP. Results: In 44 patients diagnosed with FAP (86.2%), typical pigmentation of fundus lesions were observed, in 1 patient atypical fundus changes were evident. However, in the group of patients with family history of FAP, the presence of typical fundus lesions was observed in 9 patients (25.7%). In the period of at least 6 month observation, no changes in fundus lesions were present in both groups. Conclusions: The occurrence of retinal changes typical for FAP, especially in patients with family history of the disease, should imply the higher risk of FAP.